Randomized controlled trial of educational intervention to increase consumption of vegetables by Japanese university students. Issue 4 (4th June 2018) - Ohtsuki, Makoto; Shibata, Katsumi; Fukuwatari, Tutomu; Sasaki, Yuko; Nakai, Kunihiko
Abstract : Purpose: The purpose of this paper is to evaluate the effect of an educational intervention to increase vegetable consumption by university students. Design/methodology/approach: This study is an open, parallel randomized controlled trial for 25 weeks. University students aged 18-24 years were divided into an intervention group ( n =52) and a control group ( n =52). Vegetable intake was assessed using a questionnaire. Findings: On investigation, the results indicated that the vegetable intake of the intervention group was well maintained at the end of the study, whereas that of the control group was significantly decreased by the seasonal change. This research showed that using three educational projects could significantly improve the vegetable consumption of university students. Research limitations/implications: These results suggest that the educational approach is a promising method to improve the vegetable consumption status, particularly the consumption of green and yellow vegetables, by university students. Originality/value: This parallel randomized controlled study investigated intervention via educational approaches, including a lecture on the nutritional significance of vegetable intake, a tour of an agricultural farm, and learning of cooking skills, focusing on increasing the consumption of vegetables by university students. Although there have been many intervention studies aimed at improving intake of vegetables in the world, there have been no intervention studies on the vegetable intake of young adults in Japan.